RETRACTED: The intervention of classical and molecular breeding approaches to enhance flooding stress tolerance in soybean – An review - Yijun, Guan; Zhiming, Xie; Jianing, Guan; Qian, Zhao; Rasheed, Adnan; Hussain, Muhammad Iftikhar; Ali, Iftikhar; Shuheng, Zhang; Hassan, Muhammad Umair; Hashem, Mohamed; Mostafa, Yasser S.; Wang, Yueqiang; et al. (Frontiers in Plant Science, 2022)
Abiotic stresses and climate changes cause severe loss of yield and quality of crops and reduce the production area worldwide. Flooding stress curtails soybean growth, yield, and quality and ultimately threatens the global food supply chain. Flooding tolerance is a multigenic trait. Tremendous research in molecular breeding explored the potential genomic regions governing flood tolerance in soybean. The most robust way to develop flooding tolerance in soybean is by using molecular methods, including quantitative trait loci (QTL) mapping, identification of transcriptomes, transcription factor analysis, CRISPR/Cas9, and to some extent, genome-wide association studies (GWAS), and multi-omics techniques. These powerful molecular tools have deepened our knowledge about the molecular mechanism of flooding stress tolerance. Besides all this, using conventional breeding methods (hybridization, introduction, and backcrossing) and other agronomic practices is also helpful in combating the rising flooding threats to the soybean crop. The current review aims to summarize recent advancements in breeding flood-tolerant soybean, mainly by using molecular and conventional tools and their prospects. This updated picture will be a treasure trove for future researchers to comprehend the foundation of flooding tolerance in soybean and cover the given research gaps to develop tolerant soybean cultivars able to sustain growth under extreme climatic changes.